Controlling Porosity in Lignin‐Derived Nanoporous Carbon for Supercapacitor Applications. Issue 3 (22nd October 2014) - Jeon, Ju‐Won; Zhang, Libing; Lutkenhaus, Jodie L.; Laskar, Dhrubojyoti D.; Lemmon, John P.; Choi, Daiwon; Nandasiri, Manjula I.; Hashmi, Ali; Xu, Jie; Motkuri, Radha K.; Fernandez, Carlos A.; Liu, Jian; et al.
Abstract Low‐cost renewable lignin has been used as a precursor to produce porous carbons. However, to date, it has not been easy to obtain high surface area porous carbon without activation processes or templating agents. Here, we demonstrate that low molecular weight lignin yields highly porous carbon with more graphitization through direct carbonization without additional activation processes or templating agents. We found that molecular weight and oxygen consumption during carbonization are critical factors to obtain high surface area, graphitized porous carbons. This highly porous carbon from low‐cost renewable lignin sources is a good candidate for supercapacitor electrode materials.